Cerebral Microbleeds, Vascular Risk Factors, and Magnetic Resonance Imaging Markers: The Northern Manhattan Study. Issue 9 (16th September 2016) - Caunca, Michelle R.; Del Brutto, Victor; Gardener, Hannah; Shah, Nirav; Dequatre‐Ponchelle, Nelly; Cheung, Ying Kuen; Elkind, Mitchell S. V.; Brown, Truman R.; Cordonnier, Charlotte; Sacco, Ralph L.; Wright, Clinton B.
Abstract : Background: Cerebral microbleeds (CMBs) represent intracerebral hemorrhages due to amyloid angiopathy or exposure to modifiable risk factors. Few community‐based stroke‐free studies including blacks and Hispanics have been done. Methods and Results: The Northern Manhattan Study (NOMAS) is a stroke‐free, racially and ethnically diverse cohort study. Brain MRI was performed in 1290 participants, 925 of whom had available T2* gradient‐recall echo data. We used multivariable logistic regression to examine the association of sociodemographics, vascular risk factors, apolipoprotein E (APOE) genotype, and brain MRI markers with CMB presence and location. The prevalence of CMBs in our cohort was 5%. Of the 46 participants with CMBs, 37% had only deep CMBs, 48% had only lobar CMBs, and 15% had CMBs in both locations. The difference in CMB distribution was not statistically significant across race/ethnic group or APOE genotype. In multivariable analyses, age (OR [95% CI]: 1.09 [1.04, 1.15]) and SBIs (2.58 [1.01, 6.59]) were positively associated with CMB presence, and diabetes medication use was negatively associated (0.25 [0.07, 0.86]). Conclusions: CMBs may represent the severity of vascular disease in this racially and ethnically diverse cohort. Larger studies are needed to elucidate the association between diabetes medication use and CMB presence.